Synchronous Thermogravimetry and Differential Scanning Calorimetry Estimates of Urea Inclusion Complexes Using TGA/DSC - Gupta, Gaurav; Shaikh, Vasim; Patil, Kesharsingh (Current Physical Chemistry, 2018)
Background: Urea forms channel inclusion complexes with straight chain hydrocarbon, fatty acids, etc. The decomposition of urea is an interesting thermal induced solid state reaction yielding important by-products. Urea complexation with fatty acids has been successively used in the purification and separation of fatty acids, esters and alcohols. Objective: To study the thermal gravimetry analysis behaviour for inclusion complexes of urea with stearic acid, palmitic acid and neem oil. To compute specific heat capacity at constant pressure, as a function of temperature for the studied systems. Method: The thermal gravimetry analysis and differential scanning calorimetry techniques are used. Results: Thermal profiles of adduct of fatty acid with urea indicate shift in melting temperature of urea from 408 to 413 K. Thermal profiles of urea-neem oil adduct indicating that there is some incorporation of neem oil (inclusion compound formation) by lowering the melting temperature of urea. Conclusion: The data of the corresponding weight loss and enthalpy changes for urea, fatty acids, neem oil, urea-fatty acids adduct and urea-neem oil adduct as a function of temperature are reported. The urea-fatty acid inclusion complexes show congruent behavior in melting, while for urea-neem oil inclusion complex an incongruent melting behavior is observed.
Keywords: specific heat capacity